A Novel, Layered Phase in Ti‐Rich SrTiO3 Epitaxial Thin Films. (18th December 2014) - Lee, Sungki; Damodaran, Anoop R.; Gorai, Prashun; Oh, Nuri; Moyer, Jarrett A.; Kwon, Ji‐Hwan; Ferdous, Naheed; Shah, Amish; Chen, Zuhuang; Breckenfeld, Eric; Mangalam, R. V. K.; Braun, Paul V.; et al.
<x xml:space="preserve">Abstract</x> Sr2Ti7O14, a new phase, is synthesized by leveraging the innate chemical and thermodynamic instabilities in the SrTiO3–TiO2 system and non‐equilibrium growth techniques. The chemical composition, epitaxial relationships, and orientation play roles in the formation of this novel layered phase, which, in turn, possesses unusual charge ordering, anti‐ferromagnetic ordering, and low, glass‐like thermal conductivity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>